Inventarisasi Tanaman Hias yang Berkhasiat Sebagai Obat Tradisional di Desa Anjani Kecamatan Suralaga - Hernawati Hernawati; Helmi Hariyanti; Khaerul Ihwan; Baiq Naili Dewi Atika; Pahmi Husain; Irna Il Sanuriza (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
The potential of ornamental plants can be used as Traditional medicine and does not cause side effects. It is important to take an inventory of the types of ornamental plants used as medicine by the Anjani Village community. This research method is qualitative or often referred to as Naturalistic research. Collecting data using observation and interview techniques while determining the Snow Ball Sampling technique. Data analysis was carried out interactively through the process of reducing data, display data, and verification data. The results showed that there were 14 types of ornamental plants from 12 families which were used as Traditional medicine bye pople of Anjani Village. Ornamental plants identified with herbal habits were 45% and those with shrubs and shrubs habits were 55%.